Role of the microstructure on the mechanical properties of fully pearlitic eutectoid steels - J. Toribio; B. González; J.C. Matos; F.J. Ayaso (Fracture and Structural Integrity)
This paper analyses how the microstructure of an eutectoid pearlitic steel affects its conventional mechanical properties (obtained by means of a standard tension test) and the associated micromechanisms of fracture. Results show how the yield strength, the ultimate tensile strength (UTS) and the ductility, increase as the continuous cooling rate rises, whereas on the other hand the strain at UTS decreases. The fracture surface exhibits more brittle features when the continuous cooling rate decreases, in such a manner that in the fracture process zone an increasing area appears where the pearlite lamellae can be detected and less regions of microvoids are observed.